ANALISIS Faktor PENYEBAB KECELAKAAN RUAS JALAN LIMBANGAN MALANGBONG KABUPATEN GARUT - Hernawan Hernawan; An An Anisarida (JURNAL TEKNIK SIPIL CENDEKIA (JTSC), 2022)
Accidents are unplanned and uncontrolled actions, when the action and reaction of objects, materials or radiation will cause injury or Possible injury Jalan Malangbong – Limbangan is the National route which is located on the southern route of West Java. The results of the analysis showed that the largest percentage of traffic accidents on the Malangbong Limbangan road from 2015 - 2020, the largest number of accident victims was 2015 by 33% of the number of accident victims, the placeor location of the accident occurred 63% at bends during the period 2015 - 2020, based on the type of collision by 42% when overtaking, accidents based on the most road users are motorcycles with the largest percentage from 2015 - 2020 by 58%, and 79% occurring in areas around residential areas, the largest time of occurrence is from 06.00 - 15.00 at 55 % and the main factors causing traffic accidents from year 2015 – 2020 is an environmental factor of 63% which occurs in corners due to blocked visibility and bumpy road surfaces due to heavy vehicle loads and the number of road surfaces that are temporarily repaired with patches